Neoproterozoic/Lower Palaeozoic geodynamic evolution of Dronning Maud Land: integrating geology and geophysics - Jacobs, Joachim; Läufer, Andreas; Clark, Chris; Kleinhanns, Ilka; Elburg, Marlina; Ruppel, Antonia; Estrada, Solveig; Damaske, Detlef; Jokat, Wilfried; Riedel, Sven; Lucka, Nicole (Changing polar regions : 25th International Congress on Polar Research ; March 17-22, 2013, Hamburg, Germany, 2013)
East Antarctica probably formed by amalgamation of a number of cratons along distinct Ediacaran mobile belts, including the ca. 600-500 Ma East African-Antarctic Orogen (EAAO) that dissects Dronning Maud Land (DML). New field-work during the international expeditions Geodynamic Evolution of East Antarctica (GEA) I + II in the austral summers 2010/11 and 2011/12, and first geochronological results from eastern DML reveal a complex tectonic architecture across the belt. In western DML, the EAAO reworks older Mesoproterozoic crust of the Maud Belt; the westernmost boundary of the mobile belt is characterized by a major dextral transpressional shear zone. In central DML, a major magnetic anomaly, the Forster anomaly, was interpreted as a cryptic suture of the EAAO (Riedel et al. 2012). The area where the Forster anomaly crosses the DML mountains is poorly investigated so far, but appears to coincide with a major strike slip shear zone in the southern Kurze Mts. and the occurrence of major Ediacaran granulite bodies. East of the Forster anomaly, the magnetic anomaly pattern changes significantly and typical Maud type crust is not present any longer. GEA II targeted a range of nunataks between Sør Rondane and central DML that had never been visited previously (from Blåklettane and Bergekongen in the E to Urna and Sørsteinen in the W). These nunataks are dominated by medium- to high-grade metasedimentary and metavolcanic rocks of possibly Neoproterozoic age, including abundant marble and graphite schists. Sør Rondane in eastern DML, is dominated by two distinct blocks separated by the dextral Main Shear Zone. The northwestern block is still part of the eastern EAAO, where new SHRIMP zircon data from metamorphic rims provide ages of ca. 560 Ma. The southeastern block is made up of a TTG terrane, which provides four new SHRIMP zircon dates between 990-980 Ma, interpreted as igneous crystallization ages (oceanic arc). The TTG terrane shows limited tectonic overprint and is likely the southeastern foreland of the EAAO. Close to the contact of the two blocks grey geisses and augen-gneisses gave zircon crystallization ages of ca. 750 Ma, ages which were previously unknown from the EAAO. The Forster anomaly therefore separates distinctly different parts of the EAAO: a) a reworked, mainly Grenville-age crust to the W (the overprinted margin of the Kalahari Craton) and b) a part of the orogen dominated by Neoproterozoic accretionary tectonics to the E. This difference is also reflected in the geochemistry of voluminous late-tectonics granitoids across the belt.
Keywords: Dronning Maud Land; geofysikk; geologi

Numerical simulation: The Antarctic - Grønås, Sigbjørn; Raustein, Elmer; Heinemann, Guenther (Polar lows : mesoscale weather systems in the polar regions, 2003)
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Forecasting of polar lows : aspects of forecasting specific to the Antarctic - Rasmussen, Erik A; Turner, John; Røsting, Bjørn (Polar lows : mesoscale weather systems in the polar regions, 2003)
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi

Distribution of Water Masses on the Continental Shelf in the Southern Weddell Sea - Gammelsrød, Tor; Foldvik, Arne; Nøst, Ole Anders; Foldvik, Ø.; Anderson, Leif G.; Fogelqvist, Elisabet; Olsson, K. Anders; Tanhua, Toste; Jones, Elizabeth Peter; Østerhus, Svein (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
Water properties on the continental shelf in the southern Weddell Sea observed during NARP 92/93 are presented. The station distribution includes a section close to the floating ice shelf from the Filchner Depression to the Antarctic Peninsula. Temperature, salinity, oxygen, silicate, CFC-ll and CFC-12 distributions are shown. Melting under the ice shelves, circulation systems, residence times, sediment/water interactions and bottom water formation are discussed. Ice Shelf Water (ISW), which is formed by cooling and melting below the floating ice shelf, seems to be about 10 years older than its parent water mass, which indicates the residence time below the ice shelf. The average melting rate below the Filchner Ronne ice shelf, based on the volume flux of ISW in the Filchner Depression is estimated to be 0.1 m/year. Compared with earlier observations considerable changes were found in the water characteristics and distribution: The temperature of the Weddell Deep Water has increased 0.7°C since 1977. Western Shelf Water, usually dominating the bottom layers in the Filchner Depression and on the Berkner Shelf, was found only in the Ronne Depression.
Keywords: NARP 1992/93; Sørishavet; Weddellhavet; geofysikk; oseanografi

Crustal development: Weddel Sea - Ross Sea region. Evolution of the Gondwana plate boundary in the Weddel Sea area - Kristoffersen, Yngve; Hinz, Karl (Geological evolution of Antarctica : proceedings of the Fifth International Symposium on Antarctic Earth Sciences, held at Robinson College, Cambridge, 23-28 August 1987, 1991)
Keywords: Antarktis; Weddellhavet; geofysikk; geologi; seismologi; tektonikk

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Temperature of active layer at Bunger Oasis in Antarctica in summer 1978-79 - Wójcik, Gabriel (Proceedings / Permafrost, Fifth International Conference, 1988)
Keywords: Antarktis; geofysikk; permafrost

Chemical weathering in permafrost regions of Antarctica: Great Wall Station of China, Casey Station and Davis Station of Australia - Xie, Youyu (Proceedings / Permafrost, Fifth International Conference, 1988)
Keywords: Antarktis; geofysikk; geokjemi

Absolute movements, mass balance and snow temperatures of the Riiser-Larsenisen Ice Shelf, Antarctica - Gjessing, Yngvar; Wold, Bjørn (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Oxygen isotopes and accumulation rates at Riiser-Larsenisen, Antarctica - Orheim, Olav; Gjessing, Yngvar; Lunde, Torbjørn; Repp, Kjell; Wold, Bjørn; Clausen, Henrik B; Liestøl, Olav (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Geophysical studies in the southern Weddell Sea - Haugland, Kristen; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; geofysikk

The sedimentary and volcanic sequence of Vestfjella, Dronning Maud Land - Hjelle, Audun; Winsnes, Thore S. (Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970, organized by the Scientific Committee on Antarctic Rsearch and sponsored by the International Union of Geological Sciences, 1972)
An area approximately 130 km long and 10-30 km wide along the inner part of the ice shelf in westernmost Dronning Maud Land is described. The nunataks which rise to a maximum of 1,132 m consist essentially of uniform basalt flows dipping slightly towards the west. These volcanic rocks are cut by an olivine-gabbro intrusion and several dykes and sills of Jurassic dolerite. Almost horizontal Lower Permian Beacon Supergroup sediments were found at one locality, about 20 km from the main range. There is no definite evidence that the volcanic rocks are younger than the Permian sediments; however, the chemical similarity with associated Jurassic dolerites and the general resemblance to Jurassic basalts in adjacent areas suggest that the Vestfjella volcanic rocks are also Jurassic age.
Konferansepublikasjon Series B (International Union of Geological Sciences) (0332-5172)
Keywords: Dronning Maud Land; geofysikk; geologi; sedimentologi

Nomenclature of the submarine features of the southern seas - Mosby, Håkon (Report of the Committee on the Criteria and Nomenclature of the Major Divisions of the Ocean Bottom, 1939)
Keywords: Sørishavet; geofysikk; oseanografi; topografi